Centrality and power. The struggle over the techno-political configuration of the Internet and the global digital order - Julia Pohle; Daniel Voelsen (Policy & Internet, 2022)
In recent years, various governments have been trying to subordinate the Internet to the system of the Westphalian state order. This article seeks to add a new layer to the analysis of this conflict over state sovereignty and the global digital order. It draws on network theory as an alternative analytical lens to study the reconfiguration of power relations that define the Internet as a technical, social and economic network, and its governance. We review key conflicts and developments that shaped the Internet's history, from the Internet exceptionalists' visions in the 1990s to states' recent pursuits of digital sovereignty and trace how states, as well as private companies, seek to fundamentally reconfigure the dominant logic of the Internet and its sub-networks to expand and institutionalise their power position. We thus highlight a deeper layer of conflict: the current struggles over the techno-political configuration of the Internet are not only influenced by the conflict between liberal and authoritarian visions of the Internet; they are also the result of continuous tensions between processes of centralisation and decentralisation of the Internet's technical foundations and its governance. As an effect of these dynamics, we currently witness a pluralisation of power while, at the same time, new points of centralised control emerge. – – En los últimos a\~nos, varios gobiernos han intentado subordinar Internet al sistema del orden estatal de Westfalia. Este artículo busca agregar una nueva capa al análisis de este conflicto sobre el orden digital global. Se basa en la teoría de redes como una lente analítica para estudiar la reconfiguración de las relaciones de poder que definen Internet como una red técnica, social y económica, y su gobernanza. Revisamos los conflictos clave que dieron forma a la historia de Internet, desde las visiones de los excepcionalistas de Internet en la década de 1990 hasta las búsquedas recientes de soberanía digital por parte de los estados y rastreamos cómo los estados, así como las empresas privadas, buscan reconfigurar fundamentalmente la lógica dominante de Internet y sus subredes para expandir e institucionalizar su posición de poder. Destacamos así una capa más profunda de conflicto: las luchas actuales sobre la configuración tecnopolítica de Internet no solo están influenciadas por la discrepancia entre las visiones liberal y autoritaria de Internet; también resultan de las continuas tensiones entre los procesos de centralización y descentralización de las bases técnicas de Internet y su gobernanza. Como efecto de estas dinámicas, actualmente asistimos a una pluralización del poder mientras surgen nuevos puntos de control centralizado.
Keywords: 300; digital economy; digital sovereignty; fragmentation; Internet governance; network; power; fragmentación; soberanía digital; economía digital; red; gobernanza de Internet; poder